The Role and Strategy of Islamic Religious Education in Preventing the Spread of Caliphate Ideology (Case Study in SMAN 1 Wonosobo) - Nugroho, Muhamad Yusuf Amin; Shiddiq, Ngarifin; Karwadi, Karwadi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study intends to raise two main issues, namely about the role and learning strategies of Islamic Religious Education in preventing the spread of caliphate ideology in SMA Negeri 1 Wonosobo. Using a qualitative-descriptive method, the researcher collected data through observation and interviews. This study yielded findings: In preventing the spread of the caliphate in SMA Negeri 1 Wonosobo, Islamic education learning has a significant and strategic role. Because through PAI, learning Islamic understanding and values can be instilled. Even so, the role of PAI learning cannot be separated from the role of the PAI teacher himself. The PAI learning strategy for preventing Khilafah in SMA Negeri 1 Wonosobo has been carried out through planned steps and has become part of the curriculum. The strategy is carried out through learning in and outside the classroom. Although there is no specific material on the caliphate, the teacher considers that preventing the spread of the caliphate is part of the hidden curriculum. PAI learning outside the classroom in preventing the spread of the ideology of the caliphate is carried out through several activities, namely: Formation of an Islamic Study Group, publication of the Al-Hikmah Journal, Commemoration of the Isra' Mi'raj, Commemoration of the Prophet Muhammad's Birthday, Friday sermon pulpit, Hari Raya Ceremony Santri, Seminar on religious moderation.